International Trade Unionism: The United Mine Workers in Eastern Canada, 1900-1920 - Williams, Brian (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1986)
This paper reports evidence gathered in the case ofthe United Mine Workers of America and its activities in Eastern Canada during the period 1900-1920.